Eksistensi Asas Legalitas Formil dan Materil pada KUHP Nasional - Anwar, Reski (Jurnal Fakta Hukum, 2023)
Keywords : Legality, Formal, Material, National Criminal Code Abstract : Since formal legality is frequently regarded as a truly sacred order, it is expected to adhere to a sense of justice. Moreover, the arrangements in the law should be executed no matter what that and should be treated as an impression of the side of equity. The expectation that law is equivalent to regulation and that regulation is equivalent to law is undoubtedly an exaggeration that results from this mentality and worldview. The formalistic paradigm on which this law is based makes it even more difficult to find true justice. Formal, limited, and non-binding justice exists, particularly justice that does not encompass all rights and interests, including those of victims, perpetrators, the state, and society. As a result, a number of discussions arose to investigate the legality principle, which can discuss and bridge the values that exist in society and develop. The exploration strategy utilized is standardizing juridical which is expressive logical in nature, information assortment is done with essential information as logical books and diaries and optional information as essential, auxiliary and tertiary lawful materials as the fundamental information. A qualitative analysis was carried out following the collection of the secondary and primary data. Based on the results of the data analysis, it was determined that formal legality was used to stop the authorities from acting arbitrarily against innocent people. In the mean time, the guideline of material legitimateness to connect the presence of unwritten regulations in the public eye that actually exists. Deconstruction of the principle of legality in criminal law is carried out by investigating and incorporating customary law values in order to overcome irregularities in criminal acts. In this sense, crime deviance places an emphasis not only on the unwritten law but also on legal provisions that are not in the written criminal law. Kata kunci : Legalitas, Formil, Materil, KUHP Nasional Abstrak : Legalitas formil seringkali dilihat sebagai suatu tatanan yang dianggap benar- benar sakral sehingga secara resmi harus memperhatikan rasa keadilan. Selanjutnya, pengaturan dalam undang- undang harus dilaksanakan terlepas dari itu dan harus diperlakukan sebagai gambaran dari sisi atas keadilan. Hasil dari mentalitas dan pandangan dunia ini jelas merupakan penegasan yang berlebihan dengan mengharapkan bahwa hukum adalah regulasi dan regulasi setara dengan hukum. Menemukan keadilan sejati menjadi semakin menantang karena paradigma formalistik yang menjadi landasan hukum ini. Yang ada adalah keadilan yang bersifat formal, terbatas dan tidak mengikat, khususnya keadilan yang tidak menyentuh semua hak dan kepentingan, baik kepntingan korban, pelaku, negara maupun masyarakat. Akibatnya, berbagai pembicaraan muncul untuk menyelidiki mengenai asas legalitas yang dapat membahas serta menjembatani nilai yang hidup dan berkembang di masyarakat. Metode penelitian yang digunakan adalah yuridis normatif yang sifatnya deskiptif analitik, pengumpulan data dilakukan dengan data primer berupa buku dan jurnal ilmiah dan data sekunder berupa bahan hukum primer, sekunder dan tertier sebagai data utama. Setelah data sekunder dan primer terkumpul, kemudian diadakan analisis secara kualitatif Berdasar temuan analisis data, ditentukan bahwa kedudukan legalitas formal digunakan untuk menghentikan penguasa bertindak sewenang- wenang terhadap orang yang tidak bersalah. Sementara itu, asas legalitas material untuk menjembatani adanya hukum tidak tertulis didalam masyarakat yang masih eksis ada. Untuk mengatasi penyimpangan dalam tindak pidana, dekonstruksi asas legalitas dalam hukum pidana dilakukan dengan menyelidiki dan memasukkan nilai-nilai hukum adat. Penyimpangan kejahatan dalam arti tidak hanya menekankan pada hukum tidak tertulis, tetapi juga pada ketentuan hukum yang tidak terdapat dalam hukum pidana tertulis.